What variables differentiate between selected and not selected high-performance adolescent track and field athletes? - Velez, A. E.; Garcia-Roca, J. A.; Vaquero-Cristobal, R. (Journal of Human Kinetics, 2025)
Early detection of young talent and athlete development programs lack reliable and valid indicators that can predict future success. Therefore, the aim of the present study was to analyse the differences between selected and unselected athletes to define the determinant factors, as well as the influence of gender on the variables that could predict athletic success. The research was carried out using a cross-correlational descriptive design involving 95 athletes, of whom 46 were males (average age = 18.31 ± 2.31 years) and 49 were females (averaged age = 17.27 ± 1.44 years), and whose sociodemographic, psychological, physical and anthropometric variables were analysed. Significant differences were observed in maturity (p < 0.001), anthropometric variables related to bone structure, muscle mass, and body mass (p < 0.001 to 0.044), physical condition variations related to strength, power, sprint ability, flexibility, and balance (p < 0.001 to 0.013), as well as athletic experience and training variants (p = 0.003-0.004). These results should be taken into account for the sporting programming of young athletes and in order to be aware of the modulating effect of biological maturity and its influence on athletic performance.